Review of different electrodiagnostic studies in mild carpal tunnel syndrome - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2008)
Aims: The objective of this study was to evaluate different sensory electrodiagnostic tests in mild carpal tunnel syndrome (CTS). Methods: Forty-seven patients (45 females and 2 males) with a total of 65 hands who attended the electrodiagnosis laboratory with the complaints of paresthesia, tingling, and pain in the median nerve distribution area for at least 1 month, at least 3 times/wk were included in the study. Patients with a history of CTS surgery, decreased ulnar sensory nerve action potential amplitude ( < 12 mu V), increased ulnar sensory nerve onset latency ( > 3.7 ms), increased median motor distal latency ( > 4.2 ms), polyneuropathy and/or radiculopathy, pacemaker users, and pregnant women were excluded from the study. Electrodiagnostic studies including median and ulnar motor nerve conduction velocities; median sensory nerve conduction velocity (SNCV) of the first, second, and third digit to wrist (D1-W, D2-W, and D3-W) and palm to wrist; sensory median-radial latency difference (MRD) from the thumb; sensory median-ulnar latency difference (MUD) across the wrist over 8-cm segment; and sensory median-ulnar latency difference (MUDF) from the fourth digit were performed. Results: Median SNCV of D1-W was found pathologic in all patients, MRD in 92.3%, MUDF in 92%, median SNCV of D2-W in 81.5%, MUD in 78.5%, and median SNCV of palm to wrist in 55.62%. In the case where a second test including median SNCV of D1-W, MUDF, or MRD is conducted with median SNCV of D3-W, 100%, 98%, and 97% of patients, respectively, having mild CTS could be diagnosed electrodiagnostically. Conclusions: For the electrophysiologic diagnosis of patients with probable mild CTS, adding median SNCV of D1-W, MUDF, MRD, and median SNCV of D3-W study could be suggested to increase the accuracy of the diagnosis.
Keywords: carpal tunnel syndrome; electrodiagnosis; nerve conduction studies; sensory median conduction studies; median sensory comparative tests; SENSORY CONDUCTION; NERVE-CONDUCTION; DIGITAL BRANCHES; CLASSIFICATION; SENSITIVITY; DIAGNOSIS; FINGER; TESTS